Chimpanzee behavioural flexibility and the sustainability of human-chimpanzee interactions at Cantanhez National Park, Guinea-Bissau - Hockings, Kimberley J. (2017)
UID/ANT/04038/2013 IF/01128/2014 PTDC/CS-ANT/121124/2010